2016
DOI: 10.1093/conphys/cow011
|View full text |Cite
|
Sign up to set email alerts
|

Reduced immune function predicts disease susceptibility in frogs infected with a deadly fungal pathogen

Abstract: Amphibians are susceptible to a disease-causing fungus known as Bd. We experimentally infected lowland leopard frogs to determine if Bd infection is associated with altered immune function in the blood. Our study suggests that Bd infected frogs with less active defense proteins in the blood are more susceptible to this deadly fungus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 70 publications
(97 reference statements)
0
38
0
2
Order By: Relevance
“…On one hand, natural variation in temperature impacts the expression of amphibian immunity and influences susceptibility to disease (Maniero and Carey, 1997;Raffel et al, 2006). On the other hand, warmer temperatures decrease the activity period and lifespan of Bd zoospores (Woodhams et al, 2008; Rollins-Smith et al, 2015), but they may rely on adaptive immunity, as has been shown for other frogs (Savage and Zamudio, 2011;Ellison et al, 2014;McMahon et al, 2014;Savage et al, 2016). The fact that we found a positive relationship between previous exposure and Bd infection intensity during the experiment indicates that acquired immunity may not confer full resistance to coqui frogs (Figure 4), because individuals still get infected when challenged with the pathogen at high doses.…”
Section: Discussionmentioning
confidence: 94%
“…On one hand, natural variation in temperature impacts the expression of amphibian immunity and influences susceptibility to disease (Maniero and Carey, 1997;Raffel et al, 2006). On the other hand, warmer temperatures decrease the activity period and lifespan of Bd zoospores (Woodhams et al, 2008; Rollins-Smith et al, 2015), but they may rely on adaptive immunity, as has been shown for other frogs (Savage and Zamudio, 2011;Ellison et al, 2014;McMahon et al, 2014;Savage et al, 2016). The fact that we found a positive relationship between previous exposure and Bd infection intensity during the experiment indicates that acquired immunity may not confer full resistance to coqui frogs (Figure 4), because individuals still get infected when challenged with the pathogen at high doses.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, host -pathogen interactions are much more complicated than we originally thought (figure 2), and we now must include the possibility that long co-occurrence might have allowed amphibians to develop resistance or tolerance to the pathogens, or that the pathogens have lost virulence. This is borne out by laboratory and field studies showing that prior exposure can increase survival [18,32,96] and that inherent immunogenetic variation in species [17] and populations [97] is correlated with response to disease.…”
Section: Resultsmentioning
confidence: 99%
“…In assessing the innate immune response, we found that BKA of whole blood increased with larval period. In frogs specifically, BKA predicts susceptibility to disease, specifically chytridiomycosis (Savage et al, ). Our findings indicate that post‐metamorphic amphibians might have a stronger innate immune system if they spend more time as a tadpole.…”
Section: Discussionmentioning
confidence: 99%